CLINICO-PATHOLOGICAL CO-RELATION OF MATERNAL DEATH IN RURAL AREAS OF NORTH MAHARASHTRA - M.S.VASAIKAR; S.N.KANTHIKAR; M.P.TAMBSE (International Journal of Pharma and Bio Sciences, 2014)
To study pathogenesis & morphological changes in various organs with clinico-pathological co-relations of maternal death in rural areas of North Maharashtra. To compare maternal deaths of metropolitan cities with rural areas. To evaluate several factors which are responsible for maternal death in rural areas.This was a retrospective study of 122 maternal deaths tissue received for histopathological examination over a span of 5 years (January 2008-December 2012), in government Medical college Dhule. The tissue was received from Jalgaon, Nashik, Nandurbar and Dhule districts. Ten cases were excluded from present study due to improper fixation, partial organs & ill preserved specimens. Hence 112 cases of maternal deaths were studied.Out of 112 cases, 57 cases (50.89%) died due to direct obstetric cause, 58 cases (47.32%) died due to indirect causes and in 2 cases the cause was unknown. Anemia (27.67%), Pre-eclampsia/eclampsia (28%), were the main causes of death. In 10 cases vaso-oclussive crisis due to sickle cell anemia was responsible for death. Anemia is the main cause of death in rural places of North Maharashtra, while Pre eclampsia/eclampsia is the main cause in Metropolitans cities. Thus early marriage, lack of education, ignorance has led to unutilisation of antenatal care services.